Phytoplankton in relation to physico-chemical factors in Poyang lake, Jiangxi - Dong, Hao; Liu, Jinbao (Bangladesh Journal of Botany, 2021)
Changes of phytoplankton structure and water quality were investigated in Poyang Lake from March 2014 to December 2019.The number of identified species in Poyang Lake was 187 belonging to 87 genera and 8 phyla (excluding undetermined species). Among them, Cyanophyta (74 species) had the maximum number of species, followed by Bacillariophyta (51 species) and Chlorophyta (36 species). The average numbers of phytoplankton cells were counted 2783.85 ± 458.5×104 cells/l. A total of 20 dominant species were identified in Poyang Lake, including 6 of Cyanobacteria, 6 of Diatoms, 7 of Chlorophyta, 1 of Cryptophyta and 1 of Dinoflagellates. Among phytoplankton, Cyanophyta cell density was the highest, accounting for 91.06%. Chlorophyta and diatoms accounted for 5.52 and 2.09%, respectively. The cell density of Xanthophyta was the lowest, accounting for only 0.03%. The four seasons showed obvious changes, and the order was summer - autumn - spring - winter. Algae were the most common, including green algae 153 (53%), diatoms 74 (26%), cyanobacteria 17 (17%), similar to other domestic studies. Bangladesh J. Bot. 50(3): 855-863, 2021 (September) Special